1998
DOI: 10.1115/1.2830070
|View full text |Cite
|
Sign up to set email alerts
|

Spray Cooling Enhancement by Addition of a Surfactant

Abstract: An experimental study was done on the effect of dissolving a surfactant in water sprays used to cool a hot surface. A copper surface was heated to an initial temperature of 240°C and then rapidly cooled using a spray of either pure water or an aqueous solution containing 100 ppm by weight of sodium dodecyl sulfate. The variation of surface temperature was measured during cooling, and spray impact was photographed. Addition of the surfactant was found to enhance nucleate boiling heat flux by up to 300 percent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(54 citation statements)
references
References 23 publications
4
47
2
Order By: Relevance
“…In the work of Qiao and Chandra [107] on nucleate boiling enhancement using a surfactant/water solution, the heat flux measurements could also be correlated well by scaling with T^rf-T f in a form similar to Eq. (31), q'^OSÖxlO-'iT^-Tf) 6 .…”
Section: Convective Regimementioning
confidence: 97%
“…In the work of Qiao and Chandra [107] on nucleate boiling enhancement using a surfactant/water solution, the heat flux measurements could also be correlated well by scaling with T^rf-T f in a form similar to Eq. (31), q'^OSÖxlO-'iT^-Tf) 6 .…”
Section: Convective Regimementioning
confidence: 97%
“…Other topics researched to date include the effect of surfactant addition [12,13], and secondary nucleation [9,14,17]. This work is a continuation of the enhanced surface study by Silk et al [ 181, with emphasis on straight fins as the featured surface structure geometry.…”
Section: Ken Kiger Mechanical Engineering Departmentmentioning
confidence: 69%
“…As a result, constant heat-transfer coefficient (h) is used in all analyses regardless of surface temperature. Previous studies on water spray cooling of metal substrates have shown that h is dependent on surface temperature (Qiao and Chandra 1998, Ciofalo et al 1999, Jia and Qiu 2003 and suggest that the assumption of constant h may be incorrect during transient CSC. In order to explore the heat-transfer mechanisms during CSC and to provide data at elevated initial substrate temperatures, experiments herein were performed with a Plexiglas R skin phantom coupled with a fast-response thermal sensor.…”
Section: Introductionmentioning
confidence: 99%